Elevated elephant density does not improve ecotourism opportunities: convergence in social and ecological objectives. Issue 5 (1st July 2014) - Maciejewski, Kristine; Kerley, Graham I. H.
Abstract : In order to sustainably conserve biodiversity, many protected areas, particularly private protected areas, must find means of self‐financing. Ecotourism is increasingly seen as a mechanism to achieve such financial sustainability. However, there is concern that ecotourism operations are driven to achieve successful game‐viewing, influencing the management of charismatic species. An abundance of such species, including the African elephant ( Loxodonta africana ), has been stocked in protected areas under the assumption that they will increase ecotourism value. At moderate to high densities, the impact of elephants is costly; numerous studies have documented severe changes in biodiversity through the impacts of elephants. Protected areas that focus on maintaining high numbers of elephants may therefore face a conflict between socioeconomic demands and the capacity of ecological systems. We address this conflict by analyzing tourist elephant‐sighting records from six private and one statutory protected area, the Addo Elephant National Park (AENP), in the Eastern Cape Province of South Africa, in relation to elephant numbers. We found no relationship between elephant density and elephant‐viewing success. Even though elephant density in the AENP increased over time, a hierarchical partitioning analysis indicated that elephant density was not a driver of tourist numbers. In contrast, annual tourist numbers for the AENP were positively correlated with general tourist numbers recorded for South Africa. Our results indicate that the socioeconomic and ecological requirements of protected areas in terms of tourism and elephants, respectively, converge. Thus, high elephant densities and their associated ecological costs are not required to support ecotourism operations for financial sustainability. Understanding the social and ecological feedbacks that dominate the dynamics of protected areas, particularly within private protected areas, can help to elucidate the management challenges of minimizing ecological trade‐offs while meeting ecotourist demands and achieving sustainability.